2013
DOI: 10.1002/jmri.24338
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated tool to identify the aorta and compute flow using phase‐contrast MRI: Validation and application in a large population based study

Abstract: Purpose To assess if fully automated localization of the aorta can be achieved using phase contrast (PC) magnetic resonance (MR) images. Materials and Methods PC cardiac gated MR images were obtained as part of a large population-based study. A fully automated process using the Hough transform was developed to localize the ascending aorta (AAo) and descending aorta (DAo). The study was designed to validate this technique by determining: 1) its performance in localizing the AAo and DAo; 2) its accuracy in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Manual user input is required in one image for initialization of the proposed segmentation method. A previous study has demonstrated a method for automatic identification of the ascending and descending aorta in 2D PC-MR images, assuming a strictly circular vessel lumen (Goel et al, 2014), which is not applicable on non-circular structures such as the pulmonary artery. Bratt et al (2019) recently provided proof of concept for a promising deep learning algorithm for fully automatic time-resolved segmentation of aortic blood flow with similar bias and variability as the current study.…”
Section: Comparison With Earlier Studies and Future Workmentioning
confidence: 99%
“…Manual user input is required in one image for initialization of the proposed segmentation method. A previous study has demonstrated a method for automatic identification of the ascending and descending aorta in 2D PC-MR images, assuming a strictly circular vessel lumen (Goel et al, 2014), which is not applicable on non-circular structures such as the pulmonary artery. Bratt et al (2019) recently provided proof of concept for a promising deep learning algorithm for fully automatic time-resolved segmentation of aortic blood flow with similar bias and variability as the current study.…”
Section: Comparison With Earlier Studies and Future Workmentioning
confidence: 99%
“…Automated quantitative flow analysis is dependent on the reliable identification of the vessel or region of interest, as well as its subsequent segmentation. To this end, Goel et al demonstrated the feasibility of a robust fully automated tool to localize the ascending (AAo) and descending aorta (DAo) from acquired images using the Hough transform [83]. Hough transform assigns high values to circular objects and outputs these values as a spatial density map.…”
Section: Automated Image Interpretation In Cardiologymentioning
confidence: 99%
“…Goel et al proposed a possible solution to the localization of ascending and descending aorta on 2D PC-MRI images in 2014. However, once detected, vessel lumen boundaries were approximated to a perfect circle, so that local distensibility parameters could not be calculated [12]. In the last years, other research groups proposed semi-automated methods for aortic lumen segmentation still requiring an operator to perform a manual initialization of the segmentation process [8,11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although they developed a robust localization algorithm, after being localized, the aortic lumen was just approximated as a perfect circle. For this reason, their solution did not replace previous approaches that semi-automatically segment the aorta because an accurate segmentation and the adherence to the actual anatomical structure is fundamental to evaluate local aortic elasticity parameters [12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%